Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) Kabupaten Magelang - Amar Khoerul Fahmi; Walentyna Mustika Dewi; Catur Wulandari; Ghaziah Nurika Akhni (Universitas Serang Raya, 2023)
Measurement of community satisfaction surveys in government agencies is needed as a form of community participation in assessing the performance of service providers in order to improve the quality of public services. Disdukcapil Magelang District has implemented 9 indicators of community satisfaction measurement. However, the results of the community satisfaction index still do not represent community satisfaction. This study aims to provide a new perspective on the measurement of the community satisfaction index in Disdukcapil Magelang District. The research method used is a qualitative research method with data collection techniques in the form of interviews, observations, and documentation. The theory used in this research is the five dimensions of public service quality according to Zeithaml (in Hartono, 2023), Tangibles (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy. Based on the five dimensions of service quality, the results show that there are two contradictions, namely service providers assess the dimensions of reliability, responsiveness, assurance, and empathy are good, while service recipients assess the dimensions of tangibles, responsiveness, assurance, and empathy are not good. This research is expected to be a reference for alternative measurements of community satisfaction in other public service agencies.